Assessment of vaccination service delivery and quality: a cross-sectional survey of over 1300 health facilities from 29 districts in Sindh, Pakistan conducted between 2017-18 - Danya Arif Siddiqi; Sara Abdullah; Vijay Kumar Dharma; Tasleem Khamisani; Mubarak Taighoon Shah; Hamidreza Setayesh; Aamir Javed Khan; Subhash Chandir (BMC, 2022)
Abstract Background Routine childhood immunization coverage in Pakistan remains sub-par, in part, due to suboptimal utilization of existing vaccination services. Quality of vaccine delivery can affect both supply and demand for immunization, but data for immunization center quality in Pakistan is sparse and in Sindh province in Southern Pakistan, no comprehensive health facility assessment has ever been conducted at a provincial level. We assessed health facilities, specifically immunization centers, and their associated health workers throughout the province to summarize quality of immunization centers.  Methods An exhaustive list of health facilities obtained from Sindh's provincial government was included in our analysis, comprising a total of 1396 public, private, and public-private health facilities. We adapted a health facility and health worker assessment survey developed by BASICS and EPI-Sindh to record indicators pertaining to health facility infrastructure, processes and human resources. Using expert panel ranking, we developed critical criteria (the presence of a cold box/refrigerator, vaccinator and vaccination equipment at the immunization center) to indicate the bare minimum items required by immunization centers to vaccinate children. We also categorized other infrastructure, process, and human resource items to determine high, low and moderate function requirements to ascertain quality. We evaluated presence of critical criteria, calculated scores for high, moderate and low function requirements, and displayed frequencies of infrastructure, process and human resource indicators for all immunization centers across Sindh. We analyzed results at the division level and utilized a two-sample independent clustered t-test to test differences in average function requirement scores between facilities that met critical criteria and those that did not. Results Out of the 1396 health facilities assessed across Sindh province from October 2017 to January 2018, 1236 (88.5%) were operational while 1209 (86.6%) offered vaccination services (immunization centers). Only 793 (65.6%; 793/1209) immunization centers met the critical criteria of having all the following items: vaccinator, a cold box or refrigerator and vaccine supplies. Of the 416 (34.4%; 416/1209) immunization centers that did not meet the critical criteria, most of the centers did not have a cold box or refrigerator (28.3%; 342/1209), followed by lack of vaccines (19.9%; 240/1209), and a vaccinator (13.0%; 157/1209). Of the 2153 healthcare workers interviewed, 1875 (87.1%) were vaccinators, of which 1745 (81.0%; 1745/2153) were male, and had an average of 12.4 years of schooling. A total of 1805 (96.3%; 1805/1875), 1655 (88.3%; 1655/1875) and 1387 (74.0%; 1387/1875) of the vaccinators were trained in vaccination, cold chain and inventory management respectively. Conclusion One out of three immunization centers in Sindh lack the critical components essential for quality vaccination services. While the majority of health workers (>80%) were trained on vaccination and cold chain management, the proportion trained on inventory management was comparatively low. Our findings therefore suggest that suboptimal immunization center quality is partly due to inadequate infrastructure and inefficient processes contributed to an extent, by low levels of inventory management training among vaccinators. Our study presents critical research findings with high-impact policy implications for identifying and addressing gaps to improve vaccination uptake within a low-middle income country setting.